The Medial Prefrontal Cortex, Nucleus Accumbens, Basolateral Amygdala, and Hippocampus Regulate the Amelioration of Environmental Enrichment and Cue in Fear Behavior in the Animal Model of PTSD - Ying Hao Yu; Yeou San Lim; Chen Yin Ou; Kai Chieh Chang; Arthur C. Tsai; Fang Chih Chang; Andrew Chih Wei Huang (Behavioural Neurology)
A growing body of evidence showed that environmental enrichment (EE) ameliorated footshock-induced fear behavior of posttraumatic stress disorder (PTSD). However, no research comprehensively tested the effect of EE, cue, and the combination of EE and cue in footshock-induced fear behavior of PTSD symptoms. The present study addressed this issue and examined whether the medial prefrontal cortex (mPFC, including the cingulate cortex 1 (Cg1), prelimbic cortex (PrL), and infralimbic cortex (IL)), the nucleus accumbens (NAc), the basolateral amygdala (BLA), and the hippocampus (e.g., CA1, CA3, and dentate gyrus (DG)) regulated the amelioration of the EE, cue, or the combination of EE and cue. The results showed that EE or cue could reduce fear behavior. The combination of EE and cue revealed a stronger decrease in fear behavior. The cue stimulus may play an occasion setting or a conditioned stimulus to modulate the reduction in fear behavior induced by footshock. Regarding the reduction of the EE in fear behavior, the Cg1 and IL of the mPFC and the NAc upregulated the c-Fos expression; however, the BLA downregulated the c-Fos expression. The mPFC (i.e., the Cg1, PrL, and IL) and the hippocampus (i.e., the CA1, CA3, and DG) downregulated the c-Fos expression in the suppression of the cue in fear behavior. The interaction of EE and cue in reduction of fear behavior occurred in the Cg1 and NAc for the c-Fos expression. The data of c-Fos mRNA were similar to the findings of the c-Fos protein expression. These findings related to the EE and cue modulations in fear behavior may develop a novel nonpharmacological treatment in PTSD.